2021
DOI: 10.32894/kjms.2021.169389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Primary Midline Closure and Open Surgery for Sacrococcygeal Pilonidal Sinus: A Retrospective Study

Abstract: Background: Sacrococcygeal Pilonidal sinus (SPNS) isa common problem has a variable presentation and many surgical techniques for treatment. Still, there is controversy about the best method of surgery, because of notable rates of recurrence. Objective: The aim is to clarify the better, cost-effective and less painful method for treating patients having SPNS. Methods: This is a retrospective study of 119 patients with SPNS, treated by two different surgical methods: group A (69 patients) treated with open surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The second most common procedure is excision and primary closure, as they believe that it has a faster recovery and less hospital stay, although there is a higher recurrence rate [ 15 ]. A study by Shakor et al in Suleymani-Iraq concluded that the primary closure method is more comfortable for patients than the open method and is more cost-effective [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most common procedure is excision and primary closure, as they believe that it has a faster recovery and less hospital stay, although there is a higher recurrence rate [ 15 ]. A study by Shakor et al in Suleymani-Iraq concluded that the primary closure method is more comfortable for patients than the open method and is more cost-effective [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for performing specific procedures more frequently than other procedures are that the majority agreed on specific procedures such as excision and open method because it has a lower recurrence rate (n = 45, 43.3%), safer (n = 48, 46.2%), shorter operation time (n = 40, 38.5%), and shorter hospital stay (n = 34, 32.7%). A study by Shakor et al showed that the treatment of pilonidal sinus disease by excision and the open method has a lower infection and recurrence rate than the closed method, but it is costly and more painful [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…4-Regarding rate of Complications, 9 studies [4][5][6][7][8][9][10][11][12] included comparing Complications in Lay open group versus Primary closure group. A total of 147 cases showed complications in form of infection, wound dehiscence, bleeding, scar fissure and chronic pain, with total complication rate of 19.7%, 55 cases from lay open group (16.4179%) and 92 cases from primary closure group (22.549%) with insignificant differences between the two groups regarding rate of complications.…”
Section: -As Regardmentioning
confidence: 99%